Research trends on music and advertising - Nicolas Ruth; Benedikt Spangardt (Revista Mediterránea de Comunicación, 2017)
Research on music and advertising is diverse and unstructured. Looking at the most important factors that define related research, this article aims to introduce a typology of four research fields that reflect the interplay of the complex relationship between music and advertising. An analysis of relevant studies revealed diverse research gaps and clustered the main research traditions. Eventually, we identified four types of research, namely advertising with music, advertising with musicians, music with advertising, and advertising for music. This typology leads to the conclusion that more interdisciplinary research is needed for the investigation all of the boundaries between music and advertising.